Determination of vibration transmissibility on slab track-bridge LRT Railway structure - Mat Hassan, Nik Normunira; Atil, Aida Atiqah; Roseli, Adyla Illyana; Raja Mamat, Tengku Nur Azila; Yusop, Fatimah Mohamed; Tuan Ismail, Tuan Noor Hasanah; Mohd Rus, Anika Zafiah; Marsi, Noraini; Sulong, Nurulsaidatulsyida; Mohammad Noor, Hafsa (Penerbit UTHM, 2022)
The study aims to design a new control vibration for slab track-bridge LRT railway system. This study used vibration methods by apply and analysis free and forced vibration of multiple degree of freedom and to control vibration in LRT railway system by using computation method as develop numerical solution, simulate the mode shape and natural frequency. This study as an alternative way were determined via extensive investigation that the majority of the country's railways transport had a similar problem caused by the railways, which is vibration and noise. To determine the three main unknowns, which are the mass, m, spring constant, k, and damping coefficient, c, followed by formula calculations. These values can be found, which are the Free Body Diagram (FBD), Equation of Motion, and Matrix Form of the system, as well as the Mode Shape of the Vibration Graph. MATLAB computer programming is used to generate vibration graphs. The velocity was found to be roughly 4.27mm/s, which is within the nomograph's threshold range of 3mm/s to 5mm/s. Since the value obtained from calculation which is 4.27mm/s within the threshold range, this vibration system is considered to be safe to use in the LRT station without any structural damage to occur.